2022
DOI: 10.7717/peerj.13682
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance among Streptococcus equi subspecies zooepidemicus and Rhodococcus equi isolated from equine specimens submitted to a diagnostic laboratory in Kentucky, USA

Abstract: Background Surveillance of antimicrobial resistance (AMR) among veterinary pathogens is necessary to identify clinically relevant patterns of AMR and to inform antimicrobial use practices. Streptococcus equi subsp. zooepidemicus and Rhodococcus equi are bacterial pathogens of major clinical importance in horses and are frequently implicated in respiratory tract infections. The objectives of this study were to describe antimicrobial resistance patterns and identify predictors of AMR and multidrug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…In this study Jennifer Lord and co‐workers in the United States aimed to describe antimicrobial resistance patterns and identify predictors of antimicrobial resistance (AMR) and multidrug resistance (MDR) (resistance to three or more antimicrobial classes) among equine Streptococcus zooepidemicus and Rhodococcus equi isolates .…”
Section: Antimicrobial Resistancementioning
confidence: 99%
“…In this study Jennifer Lord and co‐workers in the United States aimed to describe antimicrobial resistance patterns and identify predictors of antimicrobial resistance (AMR) and multidrug resistance (MDR) (resistance to three or more antimicrobial classes) among equine Streptococcus zooepidemicus and Rhodococcus equi isolates .…”
Section: Antimicrobial Resistancementioning
confidence: 99%
“…Beta haemolytic streptococcal isolates are commonly cultured from respiratory samples and appear to remain highly susceptible to penicillin (Isgren et al, 2021), although a recent Kentucky‐based study identified an increasing temporal trend in penicillin resistance among Streptococcus equi subsp. zooepidemicus isolates (Lord et al, 2022). However, procaine penicillin formulations have longer withdrawal times for racing and competition, and muscle soreness can develop with repeated administration.…”
mentioning
confidence: 99%